2011
DOI: 10.1021/jp206766p
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Luminescence Properties of Gold(I) and Silver(I) Dithiocarbamate Compounds

Abstract: Luminescence spectra for dithiocarbamate complexes of gold(I) and silver(I) display very different luminescence properties. At room temperature, a narrow band with a maximum at approximately 18 000 cm–1 and a broad band with a maximum at approximately 13 000 cm–1 are observed for the gold(I) and silver(I) compounds, respectively. The luminescence from the gold(I) compounds is strongly affected by external pressure, with maxima shifting to lower energy by approximately −120 cm–1/kbar. In contrast, a silver comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…The nature of the lowest-energy excited state can thus be ascribed to a LL′CT state, formed upon a transfer of electronic density from the dithiocarbamate ligand to the triphenylphosphine moiety. This is in stark contrast to the electronic structure in the presence of aurophilic interactions, where the frontier orbitals have strong M-M character [4,5]. The calculated HOMO-LUMO gap at the PBE1PBE/Lanl2dz level of theory in the gas phase is 32100 cm −1 (312 nm), suggesting a high-lying first excited state.…”
Section: Frontier Orbitalsmentioning
confidence: 72%
See 1 more Smart Citation
“…The nature of the lowest-energy excited state can thus be ascribed to a LL′CT state, formed upon a transfer of electronic density from the dithiocarbamate ligand to the triphenylphosphine moiety. This is in stark contrast to the electronic structure in the presence of aurophilic interactions, where the frontier orbitals have strong M-M character [4,5]. The calculated HOMO-LUMO gap at the PBE1PBE/Lanl2dz level of theory in the gas phase is 32100 cm −1 (312 nm), suggesting a high-lying first excited state.…”
Section: Frontier Orbitalsmentioning
confidence: 72%
“…Dithiocarbamate (dtc) complexes are attractive due to their simple structures and wide variation of luminescence properties [3][4][5]. In this note we describe a monometallic gold(I) compound with Au-dtc coordination, an example of a molecular structure without Au(I)-Au(I) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The shift in emission is attributed to a reduction in an intermolecular aurophilic interaction length from 3.42 Å at room temperature to 3.19 Å at 90 K. Time-resolved photocrystallographic studies of the copper analogue have highlighted similar structural distortions in the excited state, confirming the link between the temperature-induced structural distortion and the change in the emission spectrum (Vorontsov et al, 2005). The initial aim of the study was to compare the effect of pressure and temperature on the structure and luminescence of the complex, building on the work by various groups relating pressure-induced structural changes with dramatic shifts in the luminescence emissions in other gold(I) complexes (Paliwoda et al, 2014;Roberts et al, 2014;Baril-Robert et al, 2012). However, upon initial experiment, the complex was discovered to display an unusual form of polytypism, that is, a near isomorphic crystal structure with differences only in layer stacking (Fig.…”
Section: Introductionmentioning
confidence: 74%
“…Hydrostatic pressure is an environmental variable that has not been utilized extensively to investigate the physical and electronic properties of gold(I) trimers. It has been demonstrated that high hydrostatic pressure can be an effective tool for altering molecular geometries and hence the tuning of molecular properties in a variety of molecular materials, including energetic materials (Fabbiani & Pulham, 2006;Millar et al, 2010), molecular magnets (Parois et al, 2010;Prescimone, Milios et al, 2009;Tancharakorn et al, 2006), spin crossover systems (Shepherd et al, 2011(Shepherd et al, , 2012 and metal-organic frameworks (Moggach et al, 2009;Fairen-Jimenez et al, 2011), as well as a limited number of gold systems (Paliwoda et al, 2014;Roberts et al, 2014;Baril-Robert et al, 2012;Cairns et al, 2013). In addition to its effect on a range of properties, hydrostatic pressure is a unique tool for inducing unexpectedly complex phase behaviour in relatively simple materials, such as elemental metals (Nelmes et al, 1999;Loa et al, 2012;McMahon & Nelmes, 2006), one of the more spectacular examples being the commensurate hostguest structure of Ba at 19 GPa reported by Loa et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…as luminescent sensors [1,2]. Dithiocarbamate (dtc) complexes are attractive due to their simple structures and wide variation of luminescence properties [3][4][5]. In this note we describe a monometallic gold(I) compounds with Au-dtc coordination, an example of a molecular structure without Au(I)-Au(I) interactions.…”
Section: Introductionmentioning
confidence: 99%